2003
DOI: 10.1074/jbc.m307764200
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of the Globular Head of Complement Protein C1q Provides a Basis for Its Versatile Recognition Properties

Abstract: C1q is a versatile recognition protein that binds to an amazing variety of immune and non-immune ligands and triggers activation of the classical pathway of complement. The crystal structure of the C1q globular domain responsible for its recognition properties has now been solved and refined to 1.9 Å of resolution. The structure reveals a compact, almost spherical heterotrimeric assembly held together mainly by non-polar interactions, with a Ca 2؉ ion bound at the top. The heterotrimeric assembly of the C1q gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
374
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 323 publications
(397 citation statements)
references
References 59 publications
17
374
1
5
Order By: Relevance
“…2a). The native gC1q far-UV CD was typical of a fully β-protein consistent with the X-ray structure of the protein [18,24]. But it had the rare peculiarity of having a positive peak around 235 nm, suggesting the contributions of the side chains of aromatic residues, Trp or Tyr, to the far-UV CD [25].…”
Section: Disassembly and Unfolding Of The Gc1q Trimermentioning
confidence: 79%
See 3 more Smart Citations
“…2a). The native gC1q far-UV CD was typical of a fully β-protein consistent with the X-ray structure of the protein [18,24]. But it had the rare peculiarity of having a positive peak around 235 nm, suggesting the contributions of the side chains of aromatic residues, Trp or Tyr, to the far-UV CD [25].…”
Section: Disassembly and Unfolding Of The Gc1q Trimermentioning
confidence: 79%
“…To address this question, the gC1q domain generated by collagenase digestion of purified C1q, which is known to remain a heterotrimer after the treatment, was used as a starting material [18]. N-terminal sequence analysis of the purified material indicated that it comprises residues Gly79-Ala223 of the A chain, Gly81-Ala226 of the B chain, and Gly78-Asp217 of the C chain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 When C1q binds to IgM or clustered IgG on immunocomplexes, or to surface-bound pentraxins, other complement cascade components are sequentially activated leading to the generation of effector molecules which are able to limit infection by pathogens and play an essential homeostatic role in the clearance of damaged self-antigens, immune complexes, altered self, and apoptotic cells. 7 Besides this role in the activation of the classical complement pathway through the recognition of immune complexes, 8 it is now recognized that C1q can carry out functions that are unrelated to complement activation. Recent studies have demonstrated its involvement in several physiological processes via binding with its specific receptors.…”
Section: Introductionmentioning
confidence: 99%